Polymer mixed matrix membrane with graphene oxide for humic acid performances - Mohd Akhair, Siti Hajar; Harun, Zawati; Jamalludin, Mohd Riduan; Shuhor, Muhammad Fikri; Kamarudin, Noor Hasliza; Yunos, Muhamad Zaini; Ahmad, Azlinnorazia; Azhar, Mohd Faiz Hafeez (AIDIC-Italian Association of Chemical Engineering, 2017)
This study investigates the performance of polymer mixed matrix membrane integrated with graphene oxide (GO) towards humic acid application. Enhancement of antifouling property of polysulfone (PSf) polymer membrane can be done by integrating strong GO hydrophilicity towards hydrophobic PSf membrane. In this work GO additives were synthesized from graphite powder using variable stirring times. Meanwhile five different samples with different GO composition was fabricated via phase inversion techniques to investigate the effect of GO towards polymer mixed matrix membrane. Performances test was completed through the pure water permeability test, humic acid rejection test and anti-fouling analysis. Analysis of the results show that hydrophilic properties of the membrane increased with increasing of GO composition. Similar pattern also was observed for permeation, rejection and antifouling performances with increasing GO contents all these performances were also increased. However, concentration of GO also must be controlled to avoid the pore blockage due to GO particles agglomeration especially at higher GO concentration.